Optimalisasi Analisis Penjualan dan Prediksi Permintaan Pada UMKM dengan Business Intelligence di Kelurahan Pematang Sulur - Santoso Santoso; Niko Suwaryo; Nurali Nurali; Sandy Gunarso; Tugiman Tugiman; Agus Paryadi; Safitri Hidayah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
UMKM play an important role in the economy, but often face challenges in analyzing sales and predicting product demand. This Community Service (PkM) aims to optimize sales analysis and demand prediction in UMKM in Pematang Sulur Village, Telanaipura District, Jambi City by implementing Business Intelligence (BI). The methods used include: identification and analysis of needs by collecting sales data with surveys, training and introduction of business intelligence targeting 23 UMKM to provide more accurate insights in decision making, implementation of a business intelligence system with trend analysis, application of BI-based predictive models, mentoring and evaluation, sustainability monitoring. The results of the PkM show that the application of BI can improve operational efficiency, identify demand patterns and help UMKM in developing more appropriate business strategies. With the BI system, UMKM actors can optimize stock of goods, reduce the risk of excess or shortage of products, and increase profitability. Keywords: UMKM, Business Intelligence, Sales Analysis, Demand Prediction, Competitiveness.